2017
DOI: 10.1007/s40295-017-0116-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Revolution Solutions for the Perturbed Lambert Problem using the Method of Particular Solutions and Picard Iteration

Abstract: We present a new method for solving the multiple revolution perturbed Lambert problem using the method of particular solutions and modified ChebyshevPicard iteration. The method of particular solutions differs from the well-known Newton-shooting method in that integration of the state transition matrix (36 additional differential equations) is not required, and instead it makes use of a reference trajectory and a set of n particular solutions. Any numerical integrator can be used for solving two-point boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…t F P between the runtime for the computation of a k-th order Taylor polynomial t k D A (either map (7) or (11)) and its three for map (11). Similar results are obtained when the dynamics are propagated numerically.…”
Section: A Illustrative Examplessupporting
confidence: 63%
See 2 more Smart Citations
“…t F P between the runtime for the computation of a k-th order Taylor polynomial t k D A (either map (7) or (11)) and its three for map (11). Similar results are obtained when the dynamics are propagated numerically.…”
Section: A Illustrative Examplessupporting
confidence: 63%
“…Therefore, the proposed approach will be suitable to study the optimal insertion of corrective maneuvers for long-duration rendezvous maneuvers. Besides, the availability of high order expansions of the solution of MRPLP could be profitably used in space situational awareness to study the linkage of radar observations, as already suggested in [11]. Note that the expansion order can be tuned based on accuracy requirements, using as input the estimation of the truncation error.…”
Section: A Illustrative Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the proposed approach will be suitable to study the optimal insertion of corrective maneuvers for long-duration rendezvous maneuvers. Besides, the availability of high order expansions of the solution of MRPLP could be profitably used in space situational awareness to study the linkage of radar observations, as already suggested in [10]. Note that the expansion order can be tuned based on accuracy requirements, using as input the estimation of the truncation error.…”
Section: A Illustrative Examplesmentioning
confidence: 99%
“…Remarkably transfers with more than one thousand revolutions were presented, although limited details on how to define the continuation path were provided. Another solver suitable for MRPLP was published recently by Woollands et al [10]. This method combines the MCPI method with the method of particular solution and has the favorable property of not requiring the computation of the state transition matrix.…”
Section: Introductionmentioning
confidence: 99%